Research trends and perspectives of male infertility: a bibliometric analysis of 20 years of scientific literature. (7th July 2016) - Zhang, Y.; Xiao, F.; Lu, S.; Song, J.; Zhang, C.; Li, J.; Gu, K.; Lan, A.; Lv, B.; Zhang, R.; Mo, F.; Jiang, G.; et al.
Summary: To carry out an in‐depth analysis of the scientific research on male infertility, we performed the first bibliometric analysis focusing on studies involving male infertility worldwide during the period 1995–2014. Analysis of 6357 articles in the field of male infertility showed a significant increasing trend in the number of publications over the period 1995–2014. Obstetrics and Gynecology was an important subject category and Multidisciplinary Sciences was the newest interest. Authors were mainly from Europe and USA, with researchers from Cleveland Clinic producing the most articles, and those from the Tel Aviv Sourasky Medical Center and the University of Utah having the highest‐quality articles. The USA contributed the most independent and international collaborative articles. The Cleveland Clinic and the University of Munster were the most productive institutions. The Cleveland Clinic and the University of Giessen had the most international collaboration publications. Harvard University had the most collaborators. The most common interests were pathogenesis and therapy, and new interests were hypogonadism, obesity, and cryopreservation. In conclusion, rapid development of the male infertility field was observed. Overall, collaborative and multidisciplinary science research has become more popular. The USA and its institutions play a dominant role, followed by European countries. Thanks to the common research focus worldwide, more insight into male fertility has been gained in the scientific literature over the past 20 years. [Correction added on September 21, 2016, after online publication: the term "institute" has been replaced by the term "institution" throughout the text.]